CODE MIXING IN KISS 105 FM RADIO MEDAN - Afni Rosalina; Purwarno Purwarno; M. Manugeren (Universitas Islam Sumatera Utara (UISU), 2018)
This research deals with code mixing in kiss 105 Fm Medan. The aims are to find; (1) the type of code mixing in kiss 105 Fm Medan (2) how the announcers mix language in the process of broadcasting. Code mixing occurs when speakers mix and insert foreign words (other code) in the dominant language used (Bloomfield, 1972). The whole process of analysis is conducted with descriptive qualitative method focusing on a detailed examination of one setting or a single subject, a single depository of document, or one particular event. (Moleong, 2000). The data are from the utterances of announcers which contain code mixing during the process of broadcasting in two different radio programs; kiss weekly hot forty and movie buzz. The data are analyzed by using some steps as normally applied in descriptive qualitative method. The results show that the three types of code mixing, namely intra-sentential, intra-lexical, and a change of pronunciation are found in the utterances of the announcers. The intra sentential is dominantly found in this research. The total number of intra sentential is 38, while the total number of intra lexical is 6.